Enhancing Students’ Creative Thinking through Nearpod Integrated 5E Learning Model - Hamidilah Ridha Rahmawati; Jayanti Syahfitri; Mariana Ade Cahaya (Department of Biology Education UIN Sunan Gunung Djati Bandung, 2026)
The development of Science, Technology, and Science (IPTEKS) shows that the world is currently undergoing a very rapid transformation. Therefore, improving the quality of human resources, especially the quality of education, is an important key. Quality education produces skilled human resources, the ability to think creatively, and the readiness to face global competition. In 21st-century learning, several abilities must be developed, one of which is the ability to think creatively. Technology integration in the learning cycle 5E is needed with educational games, namely Nearpod. This study aims to determine the effect of the nearpod-based 5E learning cycle learning model on students' creative thinking abilities. The method used is an experiment with a quasi-experimental research design and a non-randomised control group pretest-posttest design. The population in this study were all students at SMA Negeri 7 Bengkulu City, with a research sample consisting of two (2) classes, namely the experimental and control classes, with a total sample of 74 students. Sampling was carried out using the purposive sampling technique. Data collection was carried out through a written test to measure students' creative thinking abilities in the form of five (5) essay questions. The data analysis technique uses a hypothesis test (t-test) with a significance level of 5% (0.05). Based on the results of the hypothesis test (t-test) on the posttest value of creative thinking ability, the value obtained is 0.000 <0.05, so there is an influence of the nearpod-based 5E learning cycle learning model on students' creative thinking abilities.